2020
DOI: 10.3390/ijms21186511
|View full text |Cite
|
Sign up to set email alerts
|

Human Natural Antibodies Recognizing Glycan Galβ1-3GlcNAc (LeC)

Abstract: The level of human natural antibodies of immunoglobulin M isotype against LeC in patients with breast cancer is lower than in healthy women. The epitope specificity of these antibodies has been characterized using a printed glycan array and enzyme-linked immunosorbent assay (ELISA), the antibodies being isolated from donors’ blood using LeC-Sepharose (LeC is Galβ1-3GlcNAcβ). The isolated antibodies recognize the disaccharide but do not bind to glycans terminated with LeC, which implies the impossibility of bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Only class G antibodies were eluted from the placenta, while IgMs were absent (IgAs were not investigated); this observation is in line with the previously published data, [39][40][41] however, in few studies, certain amounts of IgM and IgA were found in addition to predominant IgG. 42 Functional activity of IgG antibodies from healthy human placenta has been studied.…”
Section: Discussionsupporting
confidence: 84%
“…Only class G antibodies were eluted from the placenta, while IgMs were absent (IgAs were not investigated); this observation is in line with the previously published data, [39][40][41] however, in few studies, certain amounts of IgM and IgA were found in addition to predominant IgG. 42 Functional activity of IgG antibodies from healthy human placenta has been studied.…”
Section: Discussionsupporting
confidence: 84%
“…The epitope specificity of these antibodies was characterized using a printed glycan array and enzyme immunoassay; the antibodies recognized a disaccharide but did not bind to glycans ending in Le C , which implies that it is impossible to bind to ordinary glycoproteins of non-malignant cells. The antibodies had a cytotoxic effect on breast cancer cells, which suggests that anti-Le C plays a role in tumor surveillance [106].…”
Section: Detection Of Diagnostic Antibodiesmentioning
confidence: 98%
“…A number of studies show that the disaccharide LeC is a potential biomarker, as patients with BC have lower levels of nAbs (natural antibodies) of immunoglobulin M against LeC compared to healthy patients. These studies suggest that anti-LeC nAbs are involved in cancer surveillance and are believed to be cytotoxic to cancer tissues [ 48 ].…”
Section: Glycans As Biomarkers Of Breast Cancer Aggressivenessmentioning
confidence: 99%